Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1177/0162643419856275
|View full text |Cite
|
Sign up to set email alerts
|

Improving Note-Taking Skills for Students With Disabilities Through a Smartpen Intervention

Abstract: Students with disabilities (SWD; e.g., learning disabilities) often struggle with slower processing speed and poor working memory skills, which reduce the quality of their notes. This study evaluated the effects of a note-taking intervention using the researcher-created smartpen strategy in conjunction with the assistive technology of the Livescribe™ Smartpen to assess the effects of students’ overall notes and lecture comprehension. Both SWD and without disabilities in ninth-grade English Language Arts classe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 39 publications
(52 reference statements)
0
6
0
Order By: Relevance
“…While several studies (e.g., Cirillo & Hummer, 2021; Harper et al, 2017; Knox et al, 2011; Rawson et al, 2017; Tucker & Zamfir, 2021) have documented the success of smartpens in the classroom, three specific studies have shown that smartpens are an effective technology tool for students with disabilities to use to record better notes, and improve achievement (Belson et al, 2013; Boyle & Joyce, 2019; Joyce & Boyle, 2019). In the first study, Belson et al (2013) examined the notes of ten students with learning disabilities as they recorded notes using the Cornell notetaking strategy in conjunction with Echo Livescribe smartpens.…”
Section: Prior Smartpen Researchmentioning
confidence: 99%
“…While several studies (e.g., Cirillo & Hummer, 2021; Harper et al, 2017; Knox et al, 2011; Rawson et al, 2017; Tucker & Zamfir, 2021) have documented the success of smartpens in the classroom, three specific studies have shown that smartpens are an effective technology tool for students with disabilities to use to record better notes, and improve achievement (Belson et al, 2013; Boyle & Joyce, 2019; Joyce & Boyle, 2019). In the first study, Belson et al (2013) examined the notes of ten students with learning disabilities as they recorded notes using the Cornell notetaking strategy in conjunction with Echo Livescribe smartpens.…”
Section: Prior Smartpen Researchmentioning
confidence: 99%
“…Students like Nick who used the smartpen with the JIGSAW strategy reported they liked using the smartpen. One student remarked that “it was really cool to be able to go back on my notes and add what I forgot to add because I didn’t hear it well the first time so I was able to listen to it again” (Joyce, 2016, p. 77). Another common comment from students is the use of the smartpen and JIGSAW strategy helped to reduce the stress of note taking (i.e., load on working memory) and allowed students to relax while taking notes.…”
Section: Teaching Students To Use the Jigsaw Strategy With Smartpensmentioning
confidence: 99%
“…. it’s about focusing on the teacher cues” (Joyce, 2016, p. 77). Using the JIGSAW strategy with smartpens in the classroom helped students to put together pieces of and solve the note-taking puzzle (Joyce, 2016).…”
Section: Teaching Students To Use the Jigsaw Strategy With Smartpensmentioning
confidence: 99%
See 2 more Smart Citations